1998
DOI: 10.1002/(sici)1099-1387(199808)4:5<335::aid-psc155>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Solid phase synthesis of cyclic peptides: model studies involving i− ( i +4) side chain‐to‐side chain cyclisation

Abstract: Conditions for the synthesis of i-(i + 4) side chain-to-side chain head-to-tail Lys-->Glu and Glu-->Lys linked cyclic peptides related to hypoglycaemic analogues of human growth hormone hGH [6-13] have been examined. The success of the cyclisation reaction with the corresponding resin-bound, partially protected linear peptides was found to be both reagent as well as sequence dependent, with competing inter-chain oligomerisation predominating in some cases. The results also indicated that protection with the bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…However, monocyclic analogs of human calcitonin in which the side chains of aspartic acid and lysine residues in positions 17 and 21 were linked to form a 20‐atom macrocycle have consistently given much lower yields 33, 34. Similar effects of the sequence context have been reported by Hearn and co‐workers 35. These authors have also reported that the presence of an Fmoc‐protected amino acid residue immediately N‐terminal to the residues being cyclized improved the cyclization result, presumably by limiting the conformational freedom of the peptide chain during the reaction.…”
Section: Synthetic Approachessupporting
confidence: 58%
“…However, monocyclic analogs of human calcitonin in which the side chains of aspartic acid and lysine residues in positions 17 and 21 were linked to form a 20‐atom macrocycle have consistently given much lower yields 33, 34. Similar effects of the sequence context have been reported by Hearn and co‐workers 35. These authors have also reported that the presence of an Fmoc‐protected amino acid residue immediately N‐terminal to the residues being cyclized improved the cyclization result, presumably by limiting the conformational freedom of the peptide chain during the reaction.…”
Section: Synthetic Approachessupporting
confidence: 58%
“…After specific deprotection of the Lys and Glu side chains, conventional strategies can then be used to form the amide bond between the side chains. Model studies [54] on utilizing an on-resin (4-methylbenzhydryl resin) cyclization of Fmoc-Lys-Phe-D-Ala-Pro-Glu-Gly (Peptide 1) and its analogue (Peptide 2) with the positions of Lys and Glu reversed, provided the results shown in Table 2. DIC over extended times proved to be the best conditions, with peptide 1 being lactamized easier than peptide 2.…”
Section: Amide-bond Formation Via Side-chain Cyclization (Lactam Bridmentioning
confidence: 99%
“…In general, peptides and peptidomimetics may be constrained to adopt a stable β-turn conformation by the formation of linkages between the i and i + 3 positions, whereas incorporation of linkages between the i and i + 4 positions leads to stable α-helical structures . There are a very few examples of i and i + 4 lactam-bridged peptides in which turn structures appear to be preferentially stabilized; of particular note is a recent study of human calcitonin analogues in which a type-I β-turn is observed by CD . This may indicate that the stabilization of helical conformation by bridging two residues is more context-dependent than previously thought.…”
Section: Discussionmentioning
confidence: 99%